The Self And The Other In The Syrian Novel, The Emphasis On The Concept Of Power - Khaled Omar Yaseer; Ibrahim Khalil Al Shebly (دراسات فی اللغه العربیه و آدابها)
This studying focuses on the relationship between the self and the other, as it shown in this Syrian novel. This relationship is based on a logic of power.,The Syrian novel portrays the power of the other in all aspects of life including political, military and educational life, in cocontrast with the weakness of the self and its disability. It has weakened resistance mechanisms in confronting the power.